2022
DOI: 10.3390/ijerph19148493
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma and Suicide: The Mediating Effect of Stress and Sleep

Abstract: This study aimed to investigate the relationship between suicide risk, perceived stress, and sleep quality through a structural equation modeling approach. This study used convenience sampling to survey 780 undergraduate and graduate students aged 18–30 years. Students were invited to participate in the online questionnaires, which included the Beck Scale for Suicide Ideation, the Suicidal Behaviors Questionnaire-Revised, the Perceived Stress Scale, the Childhood Trauma Questionnaire-Short Form, and the Pittsb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
4
1
Order By: Relevance
“…Measuring sleep patterns during participants’ first semester of college allowed us to assess how students responded to a “sleep challenge,” and whether CM played a role in their adjustment. Of note, associations among CM, sleep, and depressive symptoms were smaller than anticipated, which may be partially attributable to the lower rates of CM reported in our sample compared to those in previous studies [ 15 , 35 ].…”
Section: Discussioncontrasting
confidence: 90%
“…Measuring sleep patterns during participants’ first semester of college allowed us to assess how students responded to a “sleep challenge,” and whether CM played a role in their adjustment. Of note, associations among CM, sleep, and depressive symptoms were smaller than anticipated, which may be partially attributable to the lower rates of CM reported in our sample compared to those in previous studies [ 15 , 35 ].…”
Section: Discussioncontrasting
confidence: 90%
“…Consistent with previous studies in the general population and people with depression, 5,47 our study demonstrated a significant positive association between all subtypes of childhood maltreatment and increased suicide ideation. Notably, our study demonstrated that emotional abuse could be a crucial vulnerability to current suicide ideation, independent of the severity of psychiatric symptoms.…”
Section: Association Between Suicide Ideation and Childhood Maltreatm...supporting
confidence: 92%
“…Further, childhood trauma was associated with increased suicidal risk in schizophrenia ( 8 , 29 ). There was supportive evidence that the association between childhood trauma and suicide was mediated by sleep quality, perceived stress, or hyperarousal symptoms ( 30 32 ).…”
Section: Introductionmentioning
confidence: 92%
“…The short-form version of the depression, anxiety, and stress scale (DASS-21) was used to measure psychological distress, including depression, anxiety, and stress in the last week. The DASS-21 subscales were divided into normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15-19), and extremely severe (>19) for anxiety; normal (0-9), mild (10)(11)(12)(13), moderate (14-20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (>27) for depression; and normal (0-14), mild (15-18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), and extremely severe (>33) for stress (19). The Chinese version of the DASS-21 for the total scale demonstrated good internal consistency, with a Cronbach's alpha of 0.95 in the Chinese population (37).…”
Section: Depression Anxiety and Stress Scalementioning
confidence: 99%